The Need to Incorporate “Akinnah” Concept as a Strategic and Holistic Module for Human Capital Development Programs for Engineering Students - Abdul Kamil, Jamaludin; Tuan Sidek, T. M.; Azizan, Ramli (The International Academic Forum (IAFOR), 2011)
The issue in human capital development is of two kinds; the interaction in physical views and spiritual enhancement. This paper discusses the second kind on how spiritual element leads to develop a notion of human capital development. Drawing from key Islamic texts, relevant prior literature, and interview with an expert, we elaborate and discuss definition of “akinnah” concept and delineate what it suggests for developing the module for a strategic and holistic program on human capital development. The study was conducted based on available published articles from Quran (sacred text), Al-Hadith (prophet said), journals, books, and other reliable sources related to the study of sustainability of human development based upon Islamic principles. The study also focuses on selected materials and concentrates on Islamic perspective and the examples presented in this article provide new information on the importance of spiritual development towards successful human capital development programs. This study is perhaps one of the first to address the definition of “akinnah” and its importance as a baseline to create a holistic module for human capital development programs.